2021
DOI: 10.2174/1573409916666191231102046
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Coumate Benzimidazole Hybrids as BRCA 1 Mimetics Through Unconventional Binding Mode; Synthesis and Preliminary Cytotoxicity Screening

Abstract: Aims: The present work focus to identify a new class of BRCA-1 mimetics that work differently from conventional anti estrogens. Background: It was found that breast cancer susceptibility protein1 (BRCA1) binds to estrogen receptor alpha (ERα) and inhibits its activity by direct interaction between domains within the amino terminus of BRCA1 and the carboxy terminus of ER alpha. Objective: A novel class of hybrids having coumate and benzimidazolone scaffolds were designed to mimic BRCA1 protein, supressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The resultant solution was stirred for 3 h at RT. It was concentrated under vacuum, the residue was dissolved in water and washed with chloroform (2X200 mL) [33] . The aqueous layer separated was basi ed with Na 2 CO 3 solution to pH10.…”
Section: Chemistrymentioning
confidence: 99%
“…The resultant solution was stirred for 3 h at RT. It was concentrated under vacuum, the residue was dissolved in water and washed with chloroform (2X200 mL) [33] . The aqueous layer separated was basi ed with Na 2 CO 3 solution to pH10.…”
Section: Chemistrymentioning
confidence: 99%
“…The antiproliferative SAR of benzimidazole‐coumarin hybrids 28 (Figure 5; IC 50 : 24.8–203.3 µM, MTT assay) against MDA‐MB‐231 cancer cell line indicated that alkyl or phenyl group at the N‐1 position of benzimidazole moiety or C‐5 position of coumarin moiety decreased the activity [ 65 ] ; the sulfonimide linker was not essential for the activity and hybrid 29 (IC 50 : 3.6 µM, MTT assay) was not inferior to doxorubicin (IC 50 : 2.2 µM) against MCF‐7 cells [ 66,67 ] ; replacement of coumarin by iminocoumarin was also tolerated and benzimidazole‐iminocoumarin hybrid 30 (IC 50 : 0.06 and 0.2 µM, MTT assay) was more potent than 5‐fluorouracil (IC 50 : 0.2 and 18.0 µM) against CEM and HeLa cancer cell lines. [ 68 ]…”
Section: Benzimidazole‐coumarin/flavonoid Hybridsmentioning
confidence: 99%
“…The antiproliferative SAR of benzimidazole-coumarin hybrids 28 (Figure 5; IC 50 : 24.8-203.3 µM, MTT assay) against MDA-MB-231 cancer cell line indicated that alkyl or phenyl group at the N-1 position of benzimidazole moiety or C-5 position of coumarin moiety decreased the activity [65] ; the sulfonimide linker was not essential for the activity and hybrid 29 (IC 50 : 3.6 µM, MTT assay) was not inferior to doxorubicin (IC 50 : 2.2 µM) against MCF-7 cells [66,67] ; replacement of coumarin by iminocoumarin was also tolerated and benzimidazoleiminocoumarin hybrid 30 (IC 50 : 0.06 and 0.2 µM, MTT assay) was more potent than 5-fluorouracil (IC 50 : 0.2 and 18.0 µM) against CEM and HeLa cancer cell lines. [68] The benzimidazole-flavonoid hybrids 31 (IC 50 : 12.0-852.0 nM, MTT assay) were highly active against SKOV3, NCI-N87, SKBR3, PC-3, MiaPaCa, HCT-116, and K562 cancer cell lines and the SAR elucidated that methyl group at N-1 position (R 1 ) decreased the activity, while chloro on the phenyl ring (R 2 ) enhanced the activity.…”
Section: Benzimidazole-coumarin/ Flavonoid Hybridsmentioning
confidence: 99%